2012
DOI: 10.4132/koreanjpathol.2012.46.1.30
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α and TNF-β Polymorphisms are Associated with Susceptibility to Osteoarthritis in a Korean Population

Abstract: BackgroundThe tumor necrosis factor (TNF) is believed to play an important role in the pathophysiology of osteoarthritis (OA). Evidence shows that genetic polymorphisms make substantial contributions to the etiology of OA.MethodsWe investigated the genotypes TNF-α and TNF-β in 301 OA patients and 291 healthy subjects as controls. We employed a polymerase chain reaction-restriction fragment length polymorphism and a polymerase chain reaction-single strand conformation polymorphism assay to identify the genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 29 publications
4
28
0
1
Order By: Relevance
“…In our study, we found that the allele 'A' of TNF-α -308 may increase the risk for OA in the Han Chinese population, which is consistent with the recent results from Korea [10], but not replicated in a Western Mexico or Turkish population [6,11]. However, rs361525 SNP (TNF-α -238) did not modulate to the susceptibility and did not contribute to the phenotype of OA in the Han Chinese population, which is consistent with the results from the Western Mexico population [6].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our study, we found that the allele 'A' of TNF-α -308 may increase the risk for OA in the Han Chinese population, which is consistent with the recent results from Korea [10], but not replicated in a Western Mexico or Turkish population [6,11]. However, rs361525 SNP (TNF-α -238) did not modulate to the susceptibility and did not contribute to the phenotype of OA in the Han Chinese population, which is consistent with the results from the Western Mexico population [6].…”
Section: Discussionsupporting
confidence: 81%
“…One study [10] observed that rs1800629 (TNF-α -308) single nucleotide polymorphism (SNP) in the TNF-α gene increased the risk for OA in a Korean population, however, another study failed to find the association of this SNP with OA in Western Mexico or the Turkish population [6,11]. Meanwhile, no significant association between rs361525 SNP (TNF-α -238) and individual susceptibility to OA in a Western Mexico population was found [6].…”
Section: Introductionmentioning
confidence: 99%
“…Among other variants of TNF-α, the minor allele of the "-308" locus is affecting the TNF-α protein expression under various stimuli 36 . Results of some previous studies unclear the association of gene variants of TNF-α with OA 13 . It was found that TNF-α can perform function independently in OA or in association with other cytokines such as IL-1β, IL-6 etc 18 .…”
Section: Gene Variants Of Tnf-α In Osteoarthritismentioning
confidence: 94%
“…Так, в работе Nakki et al установле-на связь полиморфизма rs2287047 гена рецептора IL-1 (IL1R1) c развитием ОА кисти [53]. Показа-но, что в корейской популяции полиморфные ва-рианты TNFα-G308A и TNFβ+G252A предрас-полагают к развитию ОА [47]. Попытка выявить общие гены ОА и СД была предпринята в ис-следовании Cheng et al, посвященном изучению связи полиморфизма генов PPARγ с возникнове-нием ОА и его тяжестью в франко-канадской по-пуляции [37].…”
Section: остеоартрит при диабетеunclassified